Morphometric and molecular characteristics of Labeonema synodontisi n. comb. (Nematoda: Atractidae) from the West African fishes - Koubková, Bozena; Barus, Vlastimil; Hodová, Iveta; Simková, Andrea (Parasitology research, 2008)
Numerous nematodes were found in the rectum of three fish species Synodontis ocellifer, S. nigrita, and S. schall (Mochokidae, Siluriformes) from the Gambia River and Mare Simenti, National Park Niokolo Koba, Senegal. A nematode species Raillietnema synodontisi Vassiliadès, 1973 (host S. ocellifer), is redescribed using morphometric (including scanning electron microscopy) and molecular characteristics and transferred into the genus Labeonema Puylaert, 1970. It is morphologically and metrically similar to Labeonema intermedium Puylaert, 1970, the other congeneric species (L. bainae Baker, 1982; L. bakeri Van Waerebeke, Chabaud, Bain et Georges, 1988; and L. africanum Moravec et Van As, 2004) differ from them either by the spicule and gubernaculum lengths, distribution and number of pre-cloacal papillae, position of the vulva, as well as hosts and geographical distribution. The partial sequences of small ribosomal subunit rDNA of L. synodontisi were analyzed and compared with other nematode sequences. Molecular analyses seem to support the position of this nematode species based on the morphological observation.
Keywords: Animals; RNA, Ribosomal, 18S; Female; ženské pohlaví; Microscopy, Electron, Scanning; Rhabditida; infekce hlísticemi z řádu Rhabditida; nemoci ryb; Rhabditida Infections; mikroskopie elektronová rastrovací; Molecular Sequence Data; Rivers; Fish Diseases; DNA, Helminth; sumci; molekulární sekvence - údaje; DNA helmintů; Male; řeky; RNA ribozomální 18S; Sequence Analysis, DNA; zvířata; mužské pohlaví; sekvenční analýza DNA; Africa, Western; západní Afrika; Catfishes